Risky business: A mixed methods study of decision-making regarding COVID-19 risk at a public university in the United States - Facente, Shelley N.; De Zuzuarregui, Mariah; Frank, Darren; Gomez-Aladino, Sarah; Muñoz, Ariel; Williamson, Sabrina; Wang, Emily; Hunter, Lauren; Packel, Laura; Reingold, Arthur; Petersen, Maya (Frontiers in Psychology, 2022)
Introduction Until vaccines became available in late 2020, our ability to prevent the spread of COVID-19 within countries depended largely on voluntary adherence to mitigation measures. However, individual decision-making regarding acceptable COVID-19 risk is complex. To better understand decision-making regarding COVID-19 risk, we conducted a qualitative substudy within a larger Berkeley COVID-19 Safe Campus Initiative (BCSCI) during the summer of 2020, and completed a mixed-methods analysis of factors influencing decision-making. Materials and methods We interviewed 20 participants who tested positive for SARS-CoV-2 and 10 who remained negative, and analyzed quantitative survey data from 3,324 BCSCI participants. The BCSCI study enrolled university-affiliated people living in the local area during summer of 2020, collected data on behaviors and attitudes toward COVID-19, and conducted SARS-CoV-2 testing at baseline and endline. Results At baseline, 1362 students (57.5%) and 285 non-students (35.1%) said it had been somewhat or very difficult to comply with COVID-19-related mandates. Most-cited reasons were the need to go out for food/essentials, difficulty of being away from family/friends, and loneliness. Eight interviewees explicitly noted they made decisions partially because of others who may be at high risk. We did not find significant differences between the behaviors of students and non-students. Discussion Despite prevailing attitudes about irresponsibility of college students during the COVID-19 pandemic, students in our study demonstrated a commitment to making rational choices about risk behavior, not unlike non-students around them. Decision-making was driven by perceived susceptibility to severe disease, need for social interaction, and concern about risk to others. A harm reduction public health approach may be beneficial.